ANTIOXIDANT ACTIVITY OF ALKALOID FRACTIONS OF ZANTHOXYLUM ACANTHOPODIUM DC. FRUITS WITH 1,1-DIPHENYL-2-PICRYLHYDRAZYL ASSAY - Rosidah; Zaitun Hasibuan, Poppy Anjelisa; Haro, Ginda; Masri, Puteri; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Antioxidants are vital substances which possess the ability to protect the body from damage caused by free radical-induced oxidative stress. The purpose of this study is to determine antioxidant activities of alkaloid fractions of Zanthoxylum acanthopodium DC. fruits. Methods: Z. acanthopodium DC. fruit was extracted by maceration. Ethanol extract was fractionated with liquid-liquid extraction using n-hexane and chloroform at pH 3, 7, 9, and 11 to obtained alkaloid fractions. Antioxidant activity for extract and fractions was determined with 1,1-diphenyl-2- picrylhydrazyl. Results: The IC50 of extract and fractions was 101.11±0.11, 273.24±0.12, 116.62±0.04, 61.12±0.01, 23.15±0.01, and 112.39±0.04 μg/mL, respectively. Conclusion: The results reveal that alkaloid fractions of Z. acanthopodium DC. fruit have very strong antioxidant potential. Our further study is to isolate the alkaloid compounds.